Politik Transaksional dan Pragmatisme Masyarakat Dalam Demokrasi Modern - Satryo Pringgo Sejati; Ahmad Burhan Hakim (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2024)
Democracy is a political concept that is widely used by many countries in the world today. Ideas about people's welfare are the main focus in the concept of political order in democracy. So the term democracy has become familiar to hear today. On the other hand, transactional politics is something that is often found in democracy implemented in Indonesia. This also sparked an act of political pragmatism in Indonesian society. So democracy experiences a shift in its agenda which has an impact on the quality of democracy itself. The research method used in this paper is qualitative research using a social science approach that has developed with today's modern political sciences. We also use research libraries to make it easier for us to manage data that we find and that we consider relevant. These transactional political actions are related to the attitude of the main political interest in the form of power, while the culture of political pragmatism in Indonesian society is more visible due to the relatively low level of education in Indonesian society.